Increased Posterior Tibial Slope is Associated with Revision Anterior Cruciate Ligament Reconstruction Graft Re-Rupture. Issue 7 (30th July 2021) - Ormseth, Benjamin; DiBartola, Alex; Flanigan, David; Siston, Robert; Geers, Katie; Dorweiler, Matthew; Kaeding, Christopher; Magnussen, Robert; Duerr, Robert
Objectives: Anterior cruciate ligament reconstruction (ACLR) graft failure continues to be a problem with failure rates reported up to 11%. Following revision ACLR, 3.3 – 4.3% of these patients suffer re-tear of the revision ACL graft. The purpose of this study was to evaluate the influence of posterior tibial slope (PTS) on ACL graft re-tear after revision ACLR. It was hypothesized that increased posterior tibial slope (PTS) is associated with an increased risk of ACL graft re-tear following revision ACLR. Methods: Retrospective chart review identified patients who underwent revision ACLR between 2005 and 2016 at a single institution. Patients who suffered an ACL re-tear following revision surgery were matched by age, sex, and graft type to controls who had intact revision ACLR grafts at a minimum of 2 years follow-up. Medial posterior tibial slope (MPTS) and lateral posterior tibial slope (LPTS) were measured on lateral radiographs and sagittal magnetic resonance imaging (MRI). Tibial slope was then compared between groups using independent sample t-tests. Results: Twenty-nine patients with a graft failure after revision ACLR were included and compared to 29 matched controls with a mean follow-up of 5.8 years (range: 2 to 11.3 years). Each group included 16 males and 13 females. Average age was 26 +/- 8.3 years at time of revision ACLR. Both x-ray and MRI demonstrated increased LPTS in the failure group versus controls (12.7 ± 3.2 degrees vs. 10.6 ± 3.6 degrees, p = 0.02 and 8.1 ± 3.4 degrees vs. 5.0 ± 3.5 degrees, p = 0.001, respectively). There was no significant difference in MPTS between the failure and control groups on x-ray (11.9 ± 2.9 degrees vs. 11.1 ± 3.6 degrees, p = 0.3772) nor MRI (4.3 ± 3.5 degrees vs. 3.3 ± 3.0 degrees, p = 0.2486). Conclusions: Matching for age, sex, and graft type, increased LPTS measured on both x-ray and MRI is associated with increased risk of a subsequent ACL injury following revision ACLR. Identification of at-risk patients may guide pre-operative discussions regarding revision ACL graft failure risk.